Pengaruh Pemberian Jus Buah Tomat (Solanum Lycopersicum) Terhadap Kadar Antioksidan Pada Ibu Hamil Trimester Ketiga Pascasenam Hamil - Abdul Kadir Hasan (Indonesian National Nurses Association (INNA) of Central Java, 2019)
ABSTRACTBackground. The changed that occur in anatomically and physiologically in an expectant mother in the third trimester of gestation was a normal occurrence took place. Changed was often followed by complications, if not handled properly, can be harmful to the pregnant woman and the fetus she was carrying. Complications in the third trimester of pregnancy, associated with the presence of oxidative stress, in which the third trimester increased metabolic processes, leading to increased production of free radicals. One way to reduce the complications of pregnancy and childbirth was to do the pregnancy exercise. Pregnancy exercise was the best exercise that can be done by pregnant women in labor. Pregnancy exercise was recommended at 6 months gestation entered into on and have specific movement princioles adapted to the condition of pregnantwomen. By doing pregnancy exercise excessive oxygen or not metabolizer can be used to generate energy. At 4-5% of pregnant women are not rmetabolizer residual oxygen into water and energy. The residual oxygen was the main source of ROS, especially the formation of superoxide, hydroxyl, peroxyl and hydroperoxyl anions. One nonenzimatis natural antioxidants that can be easily obtained are tomatoes. Tomatoes are loaded with vitamin C, vitamin E and beta-carotene and phenolic compounds. Besides tomatoes contain vitamin C also contain lycopene, or often referred to as α-carotene was a carotenoid. Lycopene is a powerful antioxidant that prevents damage to the natural functioning of body cells. Ability to control free radicals 100 times more efficient than vitamin E or 12.500 times that of the gluthation Method. This study was a randomized experimental study design using pretest posttest control group to see an increase in the levels of enzymatic antioxidants superoxide dismutase (SOD) in pregnant women with gestational age of 25-37 weeks. Samples that meet the inclusion and exclusion criteria consisting of 32 samples, ie 16 person control group who were not given the treatment and the treatment group was given 16 pieces of tomato juice.Result. There were influence of giving tomato juice to the antioxidation and reduced rate of Superoxide Dismutase after given tomato juice (408,39±139,05, p=304,58±79,53).Conclusion. There were side effects from tomato juice and the results of this study showed